Is Gout Associated with Pyoderma Gangrenosum? A Population-Based Case-Control Study - Kridin, Khalaf; Ludwig, Ralf J.; Tzur Bitan, Dana; Kridin, Mouhammad; Damiani, Giovanni; Cohen, Arnon D. (Journal of clinical medicine, 2020)
The coexistence of pyoderma gangrenosum (PG) and gout has been reported in individual patients; however, the association between these conditions has not been investigated. We aimed to assess the association between PG and gout and to examine whether the presence of gout predisposes to the development of PG. A population-based case-control study was conducted comparing PG patients (n = 302) with age-, sex-, and ethnicity-matched control subjects (n = 1497) with respect to the presence of preceding gout. Logistic regression models were utilized for univariate and multivariate analyses. The prevalence of preceding gout was greater in patients with PG than in control subjects (3.7% vs. 0.7%, respectively; p < 0.001). Gout was associated with a more than fivefold increase in the risk of PG (OR, 5.15; 95% CI, 2.21–11.98). After adjusting for confounding factors, gout emerged as a significant independent predictor of PG (adjusted OR, 4.08; 95% CI, 1.69–9.80). Gout preceded the diagnosis of PG by a median latency of 4.6 years. Patients with gout-associated PG were older, predominantly male, and had a higher prevalence of metabolic syndrome than other patients with PG. In conclusion, gout increases the risk of developing PG by more than fivefold. Physicians managing patients with gout and PG should be aware of this emerging association.